Polarizabilidades e parâmetros de intensidade teóricos em complexos -dicetonatos de íons Eu3+ com ligantes fosfinóxidos e 1,10- fenantrolina - Pereira, Dariston Kleber Sousa (2020)
The search for understanding the mechanisms governing the intraconfigurational 4f-4f transitions intensities in Ln3+ ions is a topic that has been widely studied. For decades, several researchers have contributed to the development of models that describe this phenomenon as precisely as possible. Among them, SOM (Simple Overlap Model) and BOM (Bond Overlap Model) consider the effects of the covalent character of the Ln3+ - ligand atom bond, which have influence on transitions intensities, in the calculation of the theoretical intensity parameters Ωλ. This work reports the theoretical study of Ωλ parameters and properties of the chemical environment for compounds of general formulas [Eu(dbm)(NO3)2(hmpa)2], [Eu(dbm)2(NO3)L2] and [Eu (dbm)3L'], where, L= hmpa (hexamethylphosphoramide), tppo (triphenylphosphine oxide), tbpo (tributylphosphine oxide) or top (trioctylphosphine oxide) and L' = hmpa or tppo, and [Eu(β-dic)(NO3)2(phen)2] and [Eu (β-dic)3(phen)], where β-dic = acac (acetylacetonate) or bzac (benzoylacetonate) and phen = 1,10-phenanthroline. The complex structures were optimized using the B3LYP methods, for compounds with dbm and Sparkle/PM3, for those with acac and bzac. Localized molecular orbital (LMO) calculations were also carried out considering the contribution of each LMO to the total polarizability, in order obtain more localized properties around the Eu3+ ion. The effective polarizabilities of each ligand were obtained considering the LMOs and their polarizabilities located in certain regions. The intensity parameters were calculated using different approaches and considering different regions, and it was also possible through these calculations to obtain the values for the overlap polarizabilities for the Eu3+ -L bonds. For such calculations, the SOM and BOM models were used. The results of the structural optimizations showed a good agreement with experimental data. It was observed in the calculations of Ωλ that very large regions of the ligands are not suitable to represent the environment close to the metal ion and that more localized regions led to values closer to the experimental ones. The methodology using BOM proved to be an important step towards obtaining theoretical intensity parameters free of adjustable parameters, which can be used in the design of new compounds.